The Candidate Blood-stage Malaria Vaccine P27A Induces a Robust Humoral Response in a Fast Track to the Field Phase 1 Trial in Exposed and Nonexposed Volunteers. (26th June 2018) - Steiner-Monard, Viviane; Kamaka, Kassim; Karoui, Olfa; Roethlisberger, Samuel; Audran, Régine; Daubenberger, Claudia; Fayet-Mello, Aurélie; Erdmann-Voisin, Aude; Felger, Ingrid; Geiger, Kristina; Govender, Lerisa; Houard, Sophie; et al.
Abstract: Background: P27A is an unstructured 104mer synthetic peptide from Plasmodium falciparum trophozoite exported protein 1 (TEX1), the target of human antibodies inhibiting parasite growth. The present project aimed at evaluating the safety and immunogenicity of P27A peptide vaccine in malaria-nonexposed European and malaria-exposed African adults. Methods: This study was designed as a staggered, fast-track, randomized, antigen and adjuvant dose-finding, multicenter phase 1a/1b trial, conducted in Switzerland and Tanzania. P27A antigen (10 or 50 μg), adjuvanted with Alhydrogel or glucopyranosil lipid adjuvant stable emulsion (GLA-SE; 2.5 or 5 μg), or control rabies vaccine (Verorab) were administered intramuscularly to 16 malaria-nonexposed and 40 malaria-exposed subjects on days 0, 28, and 56. Local and systemic adverse events (AEs) as well as humoral and cellular immune responses were assessed after each injection and during the 34-week follow-up. Results: Most AEs were mild to moderate and resolved completely within 48 hours. Systemic AEs were more frequent in the formulation with alum as compared to GLA-SE, whereas local AEs were more frequent after GLA-SE. No serious AEs occurred. Supported by a mixed Th1/Th2 cell-mediated immunity, P27A induced a marked specific antibody response able to recognize TEX1 in infected erythrocytes and to inhibit parasite growth through an antibody-dependent cellular inhibition mechanism. Incidence of AEs and antibody responses were significantly lower in malaria-exposed Tanzanian subjects than in nonexposed European subjects. Conclusions: The candidate vaccine P27A was safe and induced a particularly robust immunogenic response in combination with GLA-SE. This formulation should be considered for future efficacy trials. Clinical Trials Registration: NCT01949909, PACTR201310000683408. Abstract : P27A candidate vaccine appeared to be safe and induced a strong immunogenic response with parasite growth inhibitory capacity. The strongest specific antibody response was induced when the vaccine was formulated with glucopyranosil lipid adjuvant stable emulsion. This formulation could be considered for future efficacy trials.